Start learning 50% faster. Sign in now
Let the present age of B be x years. A’s present age = (x + 3) years C’s present age = (x - 5) years According to question, => [(x + 3) + 6]/(x - 3) = 4/3 => x = 39 C’s age, 11 years ago = (39 - 5) – 11 = 23 years
In the following questions, you will find two columns containing three sentences each. Column 1 consists of sentences A, B, and C, with one blank in on...
In each of the following questions, two columns are given containing three sentences/ phrases each. A sentence or phrase from the first column may or m...
Directions: Choose the combination that completes the sentences.
The following questions have two columns each. Match the parts correctly to form a meaningful and grammatically correct sentence.
Match the part of the sentences from column 1 with column 2 and find which of the following pair of statements given in the options make contextually an...